Costs and Benefits of Native Language Similarity for Non-native Word Learning - Marian, Viorica; Bartolotti, James; van den Berg, Aimee; Hayakawa, Sayuri (Frontiers in Psychology, 2021)
The present study examined the costs and benefits of native language similarity for non-native vocabulary learning. Because learning a second language (L2) is difficult, many learners start with easy words that look like their native language (L1) to jumpstart their vocabulary. However, this approach may not be the most effective strategy in the long-term, compared to introducing difficult L2 vocabulary early on. We examined how L1 orthographic typicality affects pattern learning of novel vocabulary by teaching English monolinguals either Englishlike or Non-Englishlike pseudowords that contained repeated orthographic patterns. We found that overall, the first words that individuals learned during initial acquisition influenced which words they acquired later. Specifically, learning a new word in one session made it easier to acquire an orthographically similar word in the next session. Similarity among non-native words interacted with native language similarity, so that words that looked more like English were easier to learn at first, but they were less effective at influencing later word learning. This demonstrates that although native language similarity has a beneficial effect early on, it may reduce learners’ ability to benefit from non-native word patterns during continued acquisition. This surprising finding demonstrates that making learning easier may not be the most effective long-term strategy. Learning difficult vocabulary teaches the learner what makes non-native words unique, and this general word form knowledge may be more valuable than the words themselves. We conclude that native language similarity modulates new vocabulary acquisition and that difficulties during learning are not always to be avoided, as additional effort early on can pay later dividends.